Remittance inflows, institutional quality, and economic growth in Nepal - Pradeep Panthi; Jeevanath Devkota (Asian Development Bank Institute (ADBI), 2023)
This study examines the impact of remittance inflows on the economic growth of Nepal using annual time series data spanning from 1993 to 2020. Moreover, it investigates the moderating role of institutional quality in this relationship. The analysis adopts the bound test approach of the cointegration and error correction model (ECM) within the autoregressive distributed lag model (ARDL) framework. The findings reveal a significant and positive influence of remittance inflows on Nepal's economic growth, despite their primary use being for consumption. Additionally, institutional quality is found to have a significant and positive association with economic growth. To support long-term economic growth, policymakers are recommended to enhance the productive utilization of remittances and strengthen institutional quality. However, it is important to note that the combined effect of remittance inflows and institutional quality may have a dampening impact on long-run economic growth, emphasizing the need for policymakers to cultivate synergy between remittance inflows and institutional development.
Keywords: C22; E51; F24; O43; 330; remittance inflows; institutional quality; economic growth; ARDL